Modelling of rheological behaviour of guava, pomelo and soursop juice concentrates via shear rate-temperature-concentration superpositioning - Abdullah, Norazlin; Nyuk, Ling Chin; Yusof, Yus Aniza; A. Talib, Rosnita (Springer Nature, 2018)
The steady-state flow test was conducted on pink-fleshed guava, pink-fleshed pomelo and soursop juice concentrates using a rheometer to understand its rheological behaviour. The power law model was used and a master-curve was created using the shear rate-temperatureconcentration superposition technique to predict rheological properties from a wide range of temperatures and concentrations. All three juice concentrates undergo a double horizontal shift whilst the pink-fleshed guava required an additional vertical shift. The final equations show shear-thinning behaviour of pink-fleshed guava, pinkfleshed pomelo and soursop with flow behaviour index of 0.2217, 0.7507 and 0.6347, respectively. The final mastercurve predicts shear stress at wide range of shear rates, i.e. between 10-2 and 106 s -1 for the pink-fleshed guava, 100 and 106 s -1 for the pink-fleshed pomelo and 100 and 107 s -1 for the soursop. The results provide useful information and effective technique to predict fruit juice concentrates behaviour affected by heat changes during processing